Persecution and suffering : Christian reflections and responses - CMS Consultation 2000 : Pune, India); Laing, Mark T. B.; Union Biblical Seminary (Pune, India). Centre for Mission Studies; I.S.P.C.K. (Organization) (Delhi : Published for Centre for Mission Studies of Union Biblical Seminary by ISPCK, 2002)
Papers presented at the 7th CMS Consultation, held in Pune from 7th to 9th Feb. 2000.
Includes bibliographical references.
Keywords: Persecution -- India -- Congresses; Suffering -- Religious aspects -- Congresses